METER : a tool for map-based visualization of referencing behaviours in scientific articles - Chew, Jesslyn Sze Yu (Nanyang Technological University, 2021)
Various citation indicators are increasingly used for measuring research performances of individuals, groups, departments, and institutions. Since citations are derived from the references in scientific articles, it is paramount to understand the referencing and citation behaviors of authors for effective usage of citations as performance indicators. In this report, we present a novel, interactive, data-driven tool called METER to aid analysis and visualization of referencing and citation behaviors of scientific articles and authors. Given a set of scientific articles of one or more authors, it overlays the referencing (i.e., cited) or citation (i.e., citing) authors and their affiliations/institutions on a Google Map and analyze their connectivity with citing or cited authors to visualize their referencing/citation behaviors (e.g., self-citation, geographical influence, possible citation circles).